2008
DOI: 10.1097/mlr.0b013e31816080e9
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Depressive Symptoms on Clinician–Patient Communication Among Patients With Type 2 Diabetes

Abstract: Diabetes patients with severe depressive symptoms are more likely than those without depressive symptoms to report suboptimal clinician-patient communication across multiple domains of communication, especially those that involve more interactive and "patient-centered" communication. Further investigation of this relationship may uncover explanatory mechanisms and help guide interventions for improving care for both conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 46 publications
3
39
1
Order By: Relevance
“…Our findings using objective measures of patient–provider communication do not strongly support studies using self-reported measures showing a link between depression and lower-quality patient–provider communication (Schenker et al, 2009; Swenson et al, 2008). However, to our knowledge, this is the first study to evaluate the effect of depressive symptoms on objective measures of patient–provider communication, which may have contributed to results that differ from previous studies evaluating subjective measures of communication alone.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings using objective measures of patient–provider communication do not strongly support studies using self-reported measures showing a link between depression and lower-quality patient–provider communication (Schenker et al, 2009; Swenson et al, 2008). However, to our knowledge, this is the first study to evaluate the effect of depressive symptoms on objective measures of patient–provider communication, which may have contributed to results that differ from previous studies evaluating subjective measures of communication alone.…”
Section: Discussioncontrasting
confidence: 99%
“…Not only are increased depressive symptoms associated with poor HIV patient outcomes (Leserman, 2008) but also based on evidence from other patient populations, depressive symptoms may also have a detrimental effect on patient–provider communication. In type II diabetes, patients with severe depressive symptoms report experiencing more verbal dominance and less patient activation and rapport building with their primary care provider than patients without depression (Swenson, Rose, Vittinghoff, Stewart, & Schillinger, 2008). Also, depressed patients with coronary artery disease were more likely to report that their provider was unresponsive to their medical treatment preferences (Schenker, Stewart, Na, & Whooley, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective analysis of data collected from 1599 patients attending 43 Scottish general practices, higher scores on the six Nottingham Health Profile dimensions of distress were significantly associated with more negative responses to questionnaire items on the doctorpatient relationship (Hopton et al, 1993). A range of other studies suggest that more negative assessments of healthcare are made by people with greater psychological distress (Bui, Ostor, Kuo, Freeman, & Goodwin, 2005;Goldzweig et al, 2010;O'Malley et al, 2005;Schenker, Stewart, Na, & Whooley, 2009;Swenson, Rose, Vittinghoff, Stewart, & Schillinger, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Our findings underscore the need for physicians to improve health communication with their patients regarding depression management. 33,34 Team-based approaches, such as collaborative depression care that provides educational materials regarding depression diagnosis, treatment, psychoeducation, and support by care managers, have been shown to significantly increase antidepressant adherence in patients with comorbid depression and diabetes, and improve disease control for both conditions. 32,35 Such interventions may succeed in part by empowering patients to become more engaged in their depression management and communicate more effectively with their providers when they are experiencing medication side effects.…”
Section: Discussionmentioning
confidence: 99%